Red squirrels use territorial vocalizations for kin discrimination - Wilson, David R.; Goble, Adam R.; Boutin, Stan; Humphries, Murray M.; Coltman, David W.; Gorrell, Jamieson C.; Shonfield, Julia; McAdam, Andrew G. (Animal behaviour, 2015)
The ability to discriminate among individuals, or among classes of individuals, can provide animals with important fitness benefits. Although several mechanisms for discrimination are possible, most require animals to show stable phenotypic variation that reflects their identity or their membership in a particular class (e.g. sex, mate, kin). For territorial animals that rarely interact physically, vocalizations could serve as long-distance signals that facilitate discrimination. In this study, we tested whether the territorial rattle vocalizations of North American red squirrels, Tamiasciurus hudsonicus, are repeatable, and whether they could hence provide the basis for multiple types of discrimination. We measured four structural features from two rattles from each of 76 marked squirrels. All four features were repeatable, which is consistent with territorial rattles being individually distinctive. We then conducted a playback experiment to determine whether squirrels use rattles for discrimination. Specifically, we tested whether squirrels discriminate between the rattles of neighbours and non-neighbours, and kin (coefficient of relatedness, r≥0.25) and non-kin (r<0.125). Following a 2×2 factorial design, we broadcast a rattle from a non-neighbouring nonkin individual to 15 subjects, from a neighbouring nonkin individual to 14 subjects, from a non-neighbouring kin individual to 11 subjects, and from a neighbouring kin individual to 13 subjects. Subjects did not discriminate between the rattles of neighbours and non-neighbours, but did respond differently to the rattles of kin and nonkin. Specifically, squirrels were significantly more likely to produce a rattle of their own in response to the broadcasted rattles of nonkin versus the broadcasted rattles of kin. This result demonstrates that red squirrels can use territorial vocalizations for kin discrimination. It also suggests that they are more tolerant of territorial intrusions by kin. •Red squirrels use rattle vocalizations during territory defence.•Rattle acoustic structure is repeatable, suggesting rattles are individually distinctive.•Squirrels do not respond differently to the rattles of neighbours and non-neighbours.•Squirrels rattle more frequently in response to the rattles of nonkin versus kin.•Red squirrels use individually distinctive rattles to discriminate kin from nonkin.